Permodelan Media Ajar Ukir Kayu Bagi Penyandang Disability Intelektual BBRSP di Temanggung - Sumino, Sumino; Mujahidin, Ahmat (Corak, 2024)
AbstractProducts made of wood such as Educational Toys, Building Puzzles, Game Block Sets in general are currently experiencing a sluggishness, especially those equipped with carvings which can be said to be stuck. Experiencing even more apprehensive conditions during the Covid-19 pandemic, apart from the reasons for government regulation of the Imposition of Restrictions on Community Activities (PPKM), it was also caused by the level of creativity of the loggers themselves who were not used to conducting Trend Forecasting, namely not carrying out the research process and formulating predictions about behavior of future users. A social institution, namely the Center for Social Rehabilitation of Persons with Intellectual Disabilities (BBRSPDI) located in Temanggung, is an education provider for persons with intellectual disabilities which is then referred to as beneficiary benefits, deems it necessary and important to have educational media and woodcarving prototypes as models for demonstration purposes or as part of the intellectual educational development process. However, since the founding of this social institution, they have never had a model of teaching media for woodcarving for reasons of not having expert instructors in carving or for reasons of inability or Low Accessibility Response for beneficiaries (students with intellectual disabilities). Woodcarving has complex processes and ornaments, so it is considered an activity that is difficult for students with disabilities to respond to. Actually, this is not the case, wood carving has a content of tiered techniques and working methods, namely Basic, Intermediate to Advanced, so it is easy to learn for someone who has never carved at all. The basic problem for disabled people is that their Intelligence Quotient (IQ) is low, so there is a delay in their reasoning power in translating images and techniques, but they still have adaptive intelligence in managing Emotional Quotient (EQ). Then it is still possible to understand even the practice of carving. Therefore the aim of this research is to design models of woodcarving teaching media that are easy for people with disabilities to respond to. The method for achieving this goal is Practice Ied Research, which is a method of combining creative practice with creative techniques and technology which outside of it is a research-based creative product, starting from a). Preparation or exploration to dig up data to concept formation (Conceptual Practices), b). Concept development to the process of making creative designs (Dialectical Practices), c) Embodiment or implementation of research results to create new products (Contextual Practices). The output targets to be achieved in this study include, a) models of teaching media made of wood including Educational Toys, Puzzles Building, Game Block Sets using carving techniques then coated with top coad of the solid Duco system or the Melamine system.AbstrakProduk-produk media edukasi berbahan kayu seperti Educational Toys, Puzzles Building, Game Block Sets pada umumnya saat ini mengalami kelesuan, apalagi yang dilengkapi dengan ukiran malahan bisa dikatakan macet. Mengalami kondisi lebih memprihatinkan dikala pandemi Covid-19, selain alasan regulasi pemerintah Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM), juga disebabkan oleh tingkat kreatifitas pelaku per-kayu-an itu sendiri yang tidak biasa melakukan Trend Forecasting yaitu tidak melakukan proses meneliti dan merumuskan prediksi tentang kebiasaan para pengguna di masa depan. Sebuah lembaga sosial yakni Balai Besar Rehabilitasi Sosial Penyandang Disability Intellectual (BBRSPDI) berlokasi di Temanggung merupakan penyelenggara pendidikan bagi penyandang disability intellectual yang kemudian disebut sebagai penerima manfaat, menganggap perlu dan penting adanya media edukasi maupun prototipe ukir kayu sebagai model untuk tujuan demonstrasi atau sebagai bagian dari proses pengembangan pendidikan intelektual. Namun semenjak berdirinya lembaga sosial tersebut belum pernah memiliki model media ajar ukir kayu karena alasan tidak memiliki instruktur ahli bidang ukir maupun karena alasan ketidakmampuan atau Low Accessibility Response bagi penerima manfaat (siswa penyandang disability intellectual). Ukir kayu memiliki kerumitan proses maupun ornamentasinya, sehingga dianggap sebagai aktivitas yang sulit direspon di kalangan siswa difabel. Sesungguhnya tidak demikian, persoalan ukir kayu memiliki muatan teknik dan metode garap berjenjang yakni Basic, Intermediate hingga Advanced, sehingga mudah untuk dipelajari bagi seseorang yang belum pernah mengukir sama sekali. Persoalan mendasar para difabel adalah Intelligence Quotients (IQ) nya rendah, sehingga ada keterlambatan daya nalar mereka dalam menterjemahkan gambar maupun teknik, tetapi masih memiliki kecerdasan adaptif dalam mengelola Emotional Quotient (EQ). Maka masih sangat mungkin untuk memahami bahkan praktik mengukir sekalipun. Metode untuk mencapai tujuan tersebut adalah Practice Ied Reseacrh, yakni metode penggabungan antara praktik kreatif dengan teknik maupun teknologi kreatif yang luarannya adalah produk kreatif berbasis penelitian, yakni mulai dari a). Persiapan atau ekplorasi untuk menggali data hingga pembentukan konsep (Conceptual Practices), b). Pengembangan konsep hingga proses pembuatan desain kreatif (Dialectical Practices), c) Perwujudan atau implementasi hasil penyelidikan untuk melahirkan produk kebaruan (Contextual Practices ). Produk dalam penelitian ini antara lain, a) model media ajar berbahan kayu meliputi produk Educational Toys, Puzzles Building, Game Block Sets.